Penyusunan Database Konstruksi Reklame Papan Berbasis Informasi Geografis (Studi Kasus: Jalan Gejayan, Jalan Kaliurang dan Jalan Monjali) - Rizky Citra Islami; Agus Nugroho (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
One of the free trading impacts in Yogyakarta is increasing the number of promotion media invarious forms, such as free standing signs, roof signs, wall signs, or suspended signs. As a tourism citythat has a market share not only domestic but also international, its usual if the  entrepreneurcontinuously compete for its product can be accepted by consumers. The used of advertisements in themain roads of Yogyakarta is one of the promotion stage. But in fact, the development of promotionmedia is almost not suitable with the procedures and even threaten the safety of road users.  Itsdiscrepancy happen because the lack of supervision from the government in Yogyakarta. In this study,researcher try to evaluate the effectiveness of billboard placement then assess its structure related tothe safety of road users. Input of the structural assessments is using the dimension of billboard and itsmaterial. From the field survey, there are 58 units of billboards at Gejayan Street, 91 unit ofbillboards at Kaliurang  Street, and 40 units of billboards at Monjali Street. The evaluation stepdetailed the pole construction and billboard side then done by structural assessment using SAP 2000.After the structural assessment is obtained, input the result of assessment into  the geographicinformation system developed by ArcGIS 10.1. The benefit of using geographic information system isthe data can be integrated from spatial map and additional information such as dimension, crosssection image, and structural assessment. The various kinds of material is dominated by steel and ironwith the range of dimension is about 0,4 until 20 m². The structural analysis result showed that 43% ofbillboards, the pole didn’t have structural reliability and the billboard’s side is not suitable tobuttress, so that they need to change their stucture. The research outcomes if its well applied, it cancontribute as evaluation tools that used by government to discipline illegal advertisement billboards.